EVALUATION OF TWO DIFFERENT INDICES USING PHOTOGRAPHIC METHOD OF ASSESSMENT OF ENAMEL DEFECTS (OPACITIES) - Khan, Hasham (Journal of Postgraduate Medical Institute, 2011)
Objective: The aim of the study was to evaluate the use of two different indices (Thylstrup and Fejerskov index and modified Developmental Defects of Enamel index) devised for measurement of enamel opacities (defects) using photographic method of assessment. Material and Methods: Using the indices, the scoring for enamel defects (on upper central incisor teeth) was made from a sample of 1000 colour photographs (slides). These photographs were of incisor teeth of 10-year-old children living in an area with water fluoride levels below 0.45 parts per million. The slides were viewed using Kodak Carousel S-A 2000 Projector. Results: Results relate to photographs of 987 children, including a total of 1957 teeth. Enamel defects that fulfilled criteria described by Thylstrup and Fejerskov as characteristic of "fluorosis" were recorded in 181(18.3%) children and 358(18.3%) upper central incisor teeth. In majority of the cases, the score was of mild fluorosis. On modified Developmental Defects of Enamel (DDE) index, 652(66.0%) children and 1086(55.5%) teeth (upper central incisors) were scored as having enamel defects. Diffuse defects were the most common. onclusion: It is concluded that both the Thylstrup and Fejerskov index and the modified Developmental Defects of Enamel (DDE) index can be used with reasonable reproducibility to measure enamel defects. However, if diffuse defects recorded on the modified DDE index were taken to be a result of fluoride intake, then fluorosis may be over-estimated in relation to fluorosis as recognized by Thylstrup and Fejerskov.